Goodnight, Goodnight, Construction Site - Rinker, Sherri Duskey; Lichtenheld, Tom (San Francisco : Chronicle Books, 2011)
At sunset, when their work is done for the day, a crane truck, a cement mixer, and other pieces of construction equipment make their way to their resting places and go to sleep.
Keywords: Construction equipment -- Juvenile fiction; Trucks -- Juvenile fiction; Stories in rhyme; Construction equipment -- Fiction; Trucks -- Fiction